2018
DOI: 10.1038/s41598-018-26335-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen protects lung from hypoxia/re-oxygenation injury by reducing hydroxyl radical production and inhibiting inflammatory responses

Abstract: Here we investigated whether hydrogen can protect the lung from chronic injury induced by hypoxia/re-oxygenation (H/R). We developed a mouse model in which H/R exposure triggered clinically typical lung injury, involving increased alveolar wall thickening, infiltration by neutrophils, consolidation, alveolar hemorrhage, increased levels of inflammatory factors and recruitment of M1 macrophages. All these processes were attenuated in the presence of H2. We found that H/R-induced injury in our mouse model was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The anti-inflammatory effect of H 2 has already been reported in many studies. In the early stage of inflammation, H 2 can reduce the infiltration of neutrophils and M1 macrophages, and the release of proinflammatory factors by downregulating the expression of intercellular cell adhesion molecule-1 (ICAM-1), granulocyte-macrophage colony-stimulating factor (GM-CSF), and granulocyte colony-stimulating factor (G-CSF) [ 4 ]. H 2 can also inhibit the expression of proinflammatory cytokines during the progress of inflammation and has been revealed in many animal models to decrease the overexpression of early proinflammatory cytokines, such as interleukin- (IL-) 1 β , IL-6, IL-8, IL-10, tumor necrosis factor-alpha (TNF- α ) [ 8 ], interferon-gamma (INF- γ ), and late proinflammatory cytokines, such as high-mobility group box-1 protein (HMGB1) [ 9 ].…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory effect of H 2 has already been reported in many studies. In the early stage of inflammation, H 2 can reduce the infiltration of neutrophils and M1 macrophages, and the release of proinflammatory factors by downregulating the expression of intercellular cell adhesion molecule-1 (ICAM-1), granulocyte-macrophage colony-stimulating factor (GM-CSF), and granulocyte colony-stimulating factor (G-CSF) [ 4 ]. H 2 can also inhibit the expression of proinflammatory cytokines during the progress of inflammation and has been revealed in many animal models to decrease the overexpression of early proinflammatory cytokines, such as interleukin- (IL-) 1 β , IL-6, IL-8, IL-10, tumor necrosis factor-alpha (TNF- α ) [ 8 ], interferon-gamma (INF- γ ), and late proinflammatory cytokines, such as high-mobility group box-1 protein (HMGB1) [ 9 ].…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%
“…Many studies using cellular, animal, and clinical experiments in a variety of biomedical fields have explored the therapeutic and preventive effects of H 2 . The collective data have indicated that H 2 is an important pathophysiological regulatory factor with antioxidative, anti-inflammatory, and antiapoptotic effects on cells and organs [ 4 6 ]. It is so convenient to use that H 2 can be easily administered in various ways, including inhalation, injection of H 2 -rich saline (HRS), drinking H 2 -rich water (HW), bathing in HW, and using HRS eyedrops.…”
Section: Introductionmentioning
confidence: 99%
“…Since the report by Ohsawa and colleagues, 5 H 2 has been used as a therapeutic antioxidant for I/R injury attenuation and organ preservation in various medical fields. [6][7][8][9][10][11][27][28][29][30][31][32] Our group previously reported the protective effects of an H 2 -rich preservation solution during cold ischemia in a rat LTx model. As a further research for clinical application, we used larger animals in this study.…”
Section: Commentmentioning
confidence: 99%
“…[6][7][8][9] Although the precise mechanism remains uncertain, the antioxidative, antiinflammatory, and antiapoptosis effects of H 2 have been reported. [10][11][12] Our group has previously reported the protective effects of an H 2 -rich solution against lung I/R injury in a rat left hilar clamp model 13 and those of an H 2 -rich lung preservation solution in a rat orthotopic left LTx model. 14 To examine the diffusion of H 2 in lungs of larger animals and evaluate the protective effects of H 2 -rich preservation solution in larger animals having much more complicated immune systems than rats, we performed this preclinical study using a canine orthotopic left LTx model.…”
mentioning
confidence: 99%
“…Treatment with molecular antioxidants reduces intracellular levels of influenza virus polymerase, providing a possible mechanism of viral titer reduction in response to antioxidant treatment (98). Additionally, it has been demonstrated that small antioxidant molecules, specifically molecular hydrogen, produce anti-inflammatory effects over multiple COVID-19 target organs, such as the lung, kidney, liver and brain, when compromised by acute and/or chronic diseases (97,(99)(100)(101)(102). For instance, a study suggested that intraperitoneal administration of hydrogen-rich saline to rats with ischemia/reperfusion-induced acute kidney injury, prevented fibrosis damage and improved renal function (99).…”
Section: Baseline Severity Progressionmentioning
confidence: 99%